Eklesiologi Hibrid Pentakostal: Liturgis, Karismatis, dan Oikoumenis : Sebuah Studi Kasus dari GSJA IES Christ the King - Welko Henro Marpaung (Indonesian Journal of Theology, 2022)
Given the massive growth of Pentecostalism did not parallel the development of Pentecostal theology, Pentecostalism needs to strengthen the articulation of the theological practices it performs. One such growth area is Pentecostal ecclesiology since churches across the Pentecostal landscape seemingly carry out such work inadequately. For this reason, the search for alternative forms of Pentecostal ecclesiology presents as a necessity. As a model for Pentecostal ecclesiology, this article presents the case study of Indonesian Assemblies of God (Gereja Sidang-sidang Jemaat Allah di Indonesia or GSJA) International English Service (IES) Christ the King (CTK). By applying a framework and process for Pentecostal spirituality as conceived by Anglican Charismatic practical theologian Mark Cartledge, GSJA IES CTK employed Cartledge’s SET (search-encounter-transformation) framework to produce a Pentecostal hybrid ecclesiology of liturgical, charismatic, and ecumenical orientation. This article discusses the background, approach, and practices of GSJA IES CTK, as well as their ecclesiological constructive process promoting the construction of an alternative Pentecostal ecclesiology.